2021
DOI: 10.1007/s00520-021-06763-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and health-related quality of life among women with breast cancer: a descriptive cross-sectional study

Abstract: Purpose Breast cancer is the most common type of cancer found in women in Sweden and worldwide. Treatment leads to increased survival of patients, but they are at risk to experience psychological distress, including anxiety and depressive symptoms, and decreased health-related quality of life (HRQoL). This study investigated the relationship between psychological distress and HRQoL and related factors among women with breast cancer in Sweden. Methods This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Emotional disorders, including anxiety and depression, are very common in breast cancer patients, with about 50% of women suffering from early-stage breast cancer dealing with anxiety, depression, or both within one year of diagnosis (Burgess et al 2005 ), which is associated with other chronic illnesses, lack of social support (Jimenez-Fonseca et al 2018 ; Yan et al 2019 ), financial difficulties, physical and cognitive decline (Gray et al 2014 ). Evidence showed that anxiety and depression are significantly correlated with reduced life quality in breast cancer patients (Nipp et al 2016 ; Phoosuwan and Lundberg 2022 ). Although these emotional disorders are prevalent and pose a serious threat to women's physical and mental health, they have rarely received clinical attention and have been managed ineffectively.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional disorders, including anxiety and depression, are very common in breast cancer patients, with about 50% of women suffering from early-stage breast cancer dealing with anxiety, depression, or both within one year of diagnosis (Burgess et al 2005 ), which is associated with other chronic illnesses, lack of social support (Jimenez-Fonseca et al 2018 ; Yan et al 2019 ), financial difficulties, physical and cognitive decline (Gray et al 2014 ). Evidence showed that anxiety and depression are significantly correlated with reduced life quality in breast cancer patients (Nipp et al 2016 ; Phoosuwan and Lundberg 2022 ). Although these emotional disorders are prevalent and pose a serious threat to women's physical and mental health, they have rarely received clinical attention and have been managed ineffectively.…”
Section: Introductionmentioning
confidence: 99%
“…The participants were selected by use of purposive sampling from a list of 481 patients with breast cancer provided by the Regional Cancer Centre in Uppsala and Örebro (Phoosuwan and Lundberg, 2022). The inclusion criteria were women (1) of age 18 years or more having no mental diseases, (2) having breast cancer diagnosis since 1-3 years and having finished treatment, (3) having undergone mastectomy, and (4) being willing to participate.…”
Section: Participantsmentioning
confidence: 99%
“…Breast reconstruction is a critical component in the treatment of patients requiring mastectomy 10 11. While curative surgery and follow-up surveillance are crucial to patients, breast reconstruction has an important role in restoring confidence, body image, rehabilitation and psychological well-being 12–16. A study on the long-term outcomes of breast reconstruction on the psychological well-being of patients showed that psychological and emotional support throughout the diagnosis and treatment plays a prominent role in the final outcome 17…”
Section: Global Health Problem Analysismentioning
confidence: 99%